Combinatorial polymer matrices enhance in vitro maturation of human induced pluripotent stem cell-derived cardiomyocytes. (October 2015) - Chun, Young Wook; Balikov, Daniel A.; Feaster, Tromondae K.; Williams, Charles H.; Sheng, Calvin C.; Lee, Jung-Bok; Boire, Timothy C.; Neely, M. Diana; Bellan, Leon M.; Ess, Kevin C.; Bowman, Aaron B.; Sung, Hak-Joon; et al.
Abstract: Cardiomyocytes derived from human induced pluripotent stem cells (iPSC-CMs) hold great promise for modeling human heart diseases. However, iPSC-CMs studied to date resemble immature embryonic myocytes and therefore do not adequately recapitulate native adult cardiomyocyte phenotypes. Since extracellular matrix plays an essential role in heart development and maturation in vivo, we sought to develop a synthetic culture matrix that could enhance functional maturation of iPSC-CMs in vitro . In this study, we employed a library of combinatorial polymers comprising of three functional subunits – poly-ε-caprolacton (PCL), polyethylene glycol (PEG), and carboxylated PCL (cPCL) – as synthetic substrates for culturing human iPSC-CMs. Of these, iPSC-CMs cultured on 4%PEG-96%PCL (each % indicates the corresponding molar ratio) exhibit the greatest contractility and mitochondrial function. These functional enhancements are associated with increased expression of cardiac myosin light chain-2v, cardiac troponin I and integrin alpha-7. Importantly, iPSC-CMs cultured on 4%PEG-96%PCL demonstrate troponin I (TnI) isoform switch from the fetal slow skeletal TnI (ssTnI) to the postnatal cardiac TnI (cTnI), the first report of such transition in vitro . Finally, culturing iPSC-CMs on 4%PEG-96%PCL also significantly increased expression of genes encoding intermediate filaments known to transduce integrin-mediated mechanical signals to the myofilaments. In summary, our study demonstrates that synthetic culture matrices engineered from combinatorial polymers can be utilized to promote in vitro maturation of human iPSC-CMs through the engagement of critical matrix-integrin interactions.